You should move `cot 2x` to the left side such that:

`tan 5x - cot 2x = 0 `

You may write `cot 2x = tan(pi/2 - 2x)` such that:

`tan 5x - tan(pi/2 - 2x) = 0 `

You need to convert the difference into a product such that:

...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You should move `cot 2x` to the left side such that:

`tan 5x - cot 2x = 0 `

You may write `cot 2x = tan(pi/2 - 2x)` such that:

`tan 5x - tan(pi/2 - 2x) = 0 `

You need to convert the difference into a product such that:

`(sin(5x - pi/2 + 2x))/(cos 5x cos (pi/2 - 2x)) = 0 `

The fraction is equal to zero if `sin(7x - pi/2) = 0` and `(cos 5x cos (pi/2 - 2x)) != 0` such that:

`sin(7x - pi/2) = 0 => 7x - pi/2 = (-1)^n arcsin 0 + npi`

`7x - pi/2 = npi => 7x = npi + pi/2 => x = npi/7 + pi/14`

**Hence, evaluating the general solution to the given equation yields `x = npi/7 + pi/14.` **